2012
DOI: 10.1590/s1678-86212012000300004
|View full text |Cite
|
Sign up to set email alerts
|

A critical view of the German procurement process in the sector

Abstract: This paper makes a critical analysis of the German procurement process in the public sector, based on a case study carried out at Karlsruhe University. The research protocol for the field study was developed in three phases: direct dialogue with the head of the department, document analysis, and semi-structured interviews. Data collection was concerned with both the analysis of the organization as well as with the mapping of project activities. A detailed study was carried out on a single construction project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…It is observed that in this study, as in the researches of Roman et al (2013) and Zanchet et al (2007), the time that does not add value (in its majority, in the form of waiting) is much higher than the time it adds value. These findings reinforce the importance of resuming the value flow mapping goal: to eliminate activities that do not add value, so that the flow of value is increasingly efficient (Hofacker et al, 2012). of Alegrete/RS City Hall.…”
Section: Map Of Future Value Flowsupporting
confidence: 60%
See 3 more Smart Citations
“…It is observed that in this study, as in the researches of Roman et al (2013) and Zanchet et al (2007), the time that does not add value (in its majority, in the form of waiting) is much higher than the time it adds value. These findings reinforce the importance of resuming the value flow mapping goal: to eliminate activities that do not add value, so that the flow of value is increasingly efficient (Hofacker et al, 2012). of Alegrete/RS City Hall.…”
Section: Map Of Future Value Flowsupporting
confidence: 60%
“…As mentioned earlier, the value stream map is the first tool to be used when thinking about introducing lean production. According to Hofacker et al (2012), the purpose of this mapping is to eliminate activities that do not add value, so that the flow of value is increasingly efficient.…”
Section: Value Flow Mapping -Vfmmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, certain authors analyse the value contributed by the university as a co-transforming agent and catalyst of innovation in its local environment (Ponsiglione et al, 2018). The public procurement process of universities, as a way of generating value in the economic environment, is also analysed from a critical perspective by the academic literature (Torres et al, 2010;Hofacker et al, 2012;Valero and Van Reenen, 2019). Van den Akker et al (2017) analyse how the response of universities to social challenges is changing the general view of the impact these institutions can have, and this is influencing their research and teaching.…”
Section: Generating and Reporting Value For Stakeholders In Higher Education Institutions Generating Value In Higher Education Institutiomentioning
confidence: 99%